Moonlighting Function of Phytochelatin Synthase1 in Extracellular Defense against Fungal Pathogens. Issue 4 (28th January 2020) - Hématy, Kian; Lim, Melisa; Cherk, Candice; Piślewska-Bednarek, Mariola; Sanchez-Rodriguez, Clara; Stein, Monica; Fuchs, Rene; Klapprodt, Christine; Lipka, Volker; Molina, Antonio; Grill, Erwin; Schulze-Lefert, Paul; et al.
Abstract : PCS1 is a moonlighting protein that functions in abiotic stress response and is indispensable for proper extracellular immune responses and pathogen-triggered glucosinolate metabolism. Abstract: Phytochelatin synthase (PCS) is a key component of heavy metal detoxification in plants. PCS catalyzes both the synthesis of the peptide phytochelatin from glutathione and the degradation of glutathione conjugates via peptidase activity. Here, we describe a role for PCS in disease resistance against plant pathogenic fungi. The pen4 mutant, which is allelic to cadmium insensitive1 ( cad1/pcs1 ) mutants, was recovered from a screen for Arabidopsis mutants with reduced resistance to the nonadapted barley fungal pathogen Blumeria graminis f. sp. hordei . PCS1, which is found in the cytoplasm of cells of healthy plants, translocates upon pathogen attack and colocalizes with the PEN2 myrosinase on the surface of immobilized mitochondria. pcs1 and pen2 mutant plants exhibit similar metabolic defects in the accumulation of pathogen-inducible indole glucosinolate-derived compounds, suggesting that PEN2 and PCS1 act in the same metabolic pathway. The function of PCS1 in this pathway is independent of phytochelatin synthesis and deglycination of glutathione conjugates, as catalytic-site mutants of PCS1 are still functional in indole glucosinolate metabolism. In uncovering a peptidase-independent function for PCS1, we reveal this enzyme to be a moonlighting protein important for plant responses to both biotic and abiotic stresses.